Students’ creative thinking skill through realistic mathematics education on straight-line equation - Rahmah Johar; Arta Maisela; Suhartati Suhartati (Jurnal Elemen, 2023)
The Indonesian students' creative thinking skill is low. One alternative to improve students' creative thinking skills is to implement realistic mathematics education. This study aimed to determine the difference in the average score of the creative thinking skills of students taught through realistic mathematics education, and students taught through the expository method on the straight-line equation topic. This study is experimental research with a post-test-only control in a class of eight-grade in one of the junior high schools in Aceh, Indonesia. The sample in this study was 30 students in the control group and 32 students in the experimental group. The instrument was a creative thinking test. The data were analyzed using a t-test. Based on the analysis, the average score of the creative thinking skill of students taught through realistic mathematics education was better than those taught through the expository method on the straight-line equation topic. Teachers are expected to guide students to solve challenging real problems to develop their creativity.